(untitled) (Research, Society and Development, 2020)
The aging process is aggravated by the presence of a high load of oxidative stress associated with the body’s imbalance concerning certain metals, with emphasis on iron. Spirulina platensis extract (SP) and caloric restriction (CR) are nutritional interventions capable to mitigate the effects of aging-related diseases. The objective of this study was to determine the effects of SP and CR against ferrous ion on the aging of Saccharomyces cerevisiae deleted of SIR2 gene. Methods: Saccharomyces cerevisiae standard (WT) and sir2Δ strains, cultured in 2% or 0.5% (CR) glucose YPD media, whether exposed to 0.8 mg/mL SP and 1mM Fe2+. Cell viability and lipoperoxidation were analyzed. Results showed reduced cell survival and increased lipid peroxidation in the SIR2 gene deletion. Statistically significant results were found after aging for WT, SP, CR, SP + Fe2+, CR + Fe2+ treatments. The therapies CR and SP showed a protective effect against ferrous ion.